The Effect Of Guided Inquiry Learning Model to Improving Student’s Interest and Learning Outcomes on Chemical Bonding Material - Paul Andohar Sipayung; Eva Marlina Ginting; Aulia Zahra Hutasuhut (Universitas Lampung, 2025)
The Effect of Guided Inquiry Learning Model on Increasing Students' Interest and Learning Outcomes in Chemical Bonding Material. This study aims to determine the effect of the Guided Inquiry model on increasing students' interest and learning outcomes in chemical bonding material. This study was conducted at SMA Negeri 1 Percut Sei Tuan, Jl. Irian Barat No. 37, Medan Estate, Percut Sei Tuan District, Deli Serdang. The sample used was students of class X-4 as the experimental class and class X-1 as the control class. The instrument used was a test instrument in the form of a multiple-choice objective test to see students' learning outcomes obtained through a posttest and a questionnaire in the form of a statement to see student’s learning interest. The results of the study showed that there was an effect of the guided inquiry model on increasing students' interest and learning outcomes in chemical bonding material. This can be seen from the results of the posttest hypothesis test using the t-test obtained that tcount> ttable = 9.6 > 1.6. The results of the study of students' learning interests using the t-test obtained a calculated tcount> ttable = 5.6 > 1.6. The relationship between interest and student learning outcomes shows a correlation of 0.62 (high correlation).